2015
DOI: 10.3389/fncel.2015.00278
|View full text |Cite
|
Sign up to set email alerts
|

Elusive roles for reactive astrocytes in neurodegenerative diseases

Abstract: Astrocytes play crucial roles in the brain and are involved in the neuroinflammatory response. They become reactive in response to virtually all pathological situations in the brain such as axotomy, ischemia, infection, and neurodegenerative diseases (ND). Astrocyte reactivity was originally characterized by morphological changes (hypertrophy, remodeling of processes) and the overexpression of the intermediate filament glial fibrillary acidic protein (GFAP). However, it is unclear how the normal supportive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
293
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(302 citation statements)
references
References 295 publications
(366 reference statements)
4
293
1
4
Order By: Relevance
“…Outward manifestation of reactive gliosis/neuro inflammatory processes are associated with head trauma (Lopez-Rodriguez, Acaz-Fonseca, 2015), ischemia (Li, Xu, 2015c) infection (Ben Haim, Carrillo-de Sauvage, 2015a) and neuronal lesions infiltrated with protein aggregates such as amyloid β (Aβ), neurofibrillary tangles (Ben Haim, Carrillo-de Sauvage, 2015a) α-synucleinA53T (Ben Haim, Carrillo-de Sauvage, 2015a, Yang, Wang, 2015) which are common to AD and PD pathologies, respectively. Sustained neuro-inflammatory processes can be perpetuated by dying cells which release DAMPs such as high mobility group box-1 (HMGB1)/capable of activating innate immunity to remove necrotic debris, then worsening the neurodegenerative process (Frank, Adhikary, 2016, Kigerl, de Rivero Vaccari, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outward manifestation of reactive gliosis/neuro inflammatory processes are associated with head trauma (Lopez-Rodriguez, Acaz-Fonseca, 2015), ischemia (Li, Xu, 2015c) infection (Ben Haim, Carrillo-de Sauvage, 2015a) and neuronal lesions infiltrated with protein aggregates such as amyloid β (Aβ), neurofibrillary tangles (Ben Haim, Carrillo-de Sauvage, 2015a) α-synucleinA53T (Ben Haim, Carrillo-de Sauvage, 2015a, Yang, Wang, 2015) which are common to AD and PD pathologies, respectively. Sustained neuro-inflammatory processes can be perpetuated by dying cells which release DAMPs such as high mobility group box-1 (HMGB1)/capable of activating innate immunity to remove necrotic debris, then worsening the neurodegenerative process (Frank, Adhikary, 2016, Kigerl, de Rivero Vaccari, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These are known to include specific targets such as janus kinase/signal transducer and activator of transcription (JAK/STAT) (Ben Haim, Carrillo-de Sauvage, 2015a, Ben Haim et al, 2015b, Wang et al, 2015b), nuclear Factor of Kappa light polypeptide gene enhancer in B-cells (NF-κB), calcineurin, Mitogen-Activated Protein Kinases (MAPKs) (Ben Haim, Carrillo-de Sauvage, 2015a) or Notch1-STAT3-ETB (LeComte et al, 2015). These are the indirect controls account for biological events such as induction of iNOS, release of NO, MCP-1 and CINCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some studies have shown abstinence-induced decreases in cortical astrocytes, increases in nucleus accumbens astrocytes, and others show no change in astrocytes (Bull et al, 2014; Miguel-Hidalgo, 2006; Miguel-Hidalgo et al, 2002). The ramifications of density changes in astrocytes, as measured by GFAP expression, is not yet fully understood, but may reflect the engagement of astrocytes in inflammatory signaling (see above) or represent changes in astrocyte functioning at the perisynaptic sites (Ben Haim et al, 2015). …”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%
“…Desempenham funções importantes, tais como a sustentação e a nutrição dos neurônios, além de serem reguladores das funções neuronais (BEN HAIM et al, 2015).…”
Section: Pg/ml)unclassified